Lean and Seamless - A, Kovindha (ASEAN Journal of Rehabilitation Medicine, 2020)
In rehabilitation, an ultimate goal is to restore functions of an individual so that he/she reaches independency in performing activities in daily life and has better quality of life. To achieve the goal, rehabilitation physicians (physiatrists) as well as other rehabilitation professionals should learn and apply business knowledge and skills to improve rehabilitation services so that those who need rehabilitation could access to the services and truly get benefits. In business, a lean process is a method of eliminating wasteful practices to improve service efficiency and effectiveness. The concept of lean has been implemented in healthcare services including rehabilitation as rehabilitation services delivered by rehabilitation team of multi-professionals are complex. Many processes may be unnecessary and should be removed. All professionals involved have to work together to set common goals and to produce a coordinated set of therapy. Among rehabilitation professionals, nurses and occupational therapists both work to improve patients’ performance in self-care. Each discipline has one’s own principles of approach. Breaking down boundaries and complexity would lead to a seamless flow of services, and thus benefit the patients. The concept of seamless patient care consists of consistency, continuity and coordination of care that should be implemented across the whole work processes. Self-care by nurses and self-care training by occupational therapists may vary and confuse patients. Cross functional communication is necessary to provide well-coordinated, consistent and continuous services across disciplines. Moreover, all in the team should work together to clarify responsibilities, care objectives, and treatment plans. In this issue, there is an interesting research study reporting a successful seamless care and training in self-care between nurses and occupational therapists. The seamless self-care training firstly delivered by occupational therapists is continued consistently and efficiently by nurses, and efficiently makes patients with stroke effectively achieve independency in dressing within a short period of time. This seamless care may be an appropriate solution for hospitals where a number of occupational therapists is limited. Lastly, just reading the article makes readers learn and know more but a true success is to apply it in real practice.